Ultrasonic grain refinement of die cast copper alloys - Puga, Hélder (2019)
In this study, the effect of ultrasound as an alternative melt refinement technique of commercially available brass alloys and its impact in the microstructural and mechanical properties is analysed. A Cu-Zn alloy was cast in different conditions: without melt treatment, chemically refined and ultrasonically refined at different temperatures. Ultrasonic treatment was found to be more efficient than chemical refinement, promoting lower grain size and higher roundness of the α-phase and decreased the ratio of the α/β phases. The best results were achieved for 940 °C melt refinement temperature. The microstructure morphology improved the alloy mechanical properties, namely ultimate tensile strength, yield stress and elongation, which attained 386 MPa, 192 MPa and 11.5%, respectively, for that melt refinement temperature.